Hidup Sehat dan Bugar Pada Usia Lansia di Panti Sosial Rumoh Seujahtera Geunaseh Sayang, Banda Aceh - Satria Safirza; Elmiyati; Ratih Ayu Atika; Syarifah Nora Andriaty; Farid Bastian; Ade Kiki Riezky; Meri Lidyawati; Iziddin Fadhil (Jurnal Ragam Pengabdian, 2025)
The elderly are a population group that is vulnerable to various degenerative diseases due to the aging process. The importance of elderly knowledge about healthy and fit lifestyles will affect the health and quality of life of the elderly. Education about healthy lifestyles has a crucial role in helping the elderly understand and implement healthy lifestyle behaviors. Through a good educational approach, it will help the elderly understand how to behave in a healthy and fit lifestyle in old age. The importance of knowledge such as a balanced nutritious diet, stress management, elderly exercise and routine health checks can improve the morbidity and mortality rates of the elderly living in sosial  institutions. In direct observation, the elderly at the Rumoh Seujahtera Geunaseh Sayang Sosial  Institution in Banda Aceh do not fully understand the optimal healthy and fit lifestyle in old age in their daily lives, this is seen by there are still elderly who only sit pensive without doing healthy and fit lifestyle activities in their free time. This service method is carried out through counseling methods and the elderly at the Rumoh Seujahtera Geunaseh Sayang Sosial  Institution in Banda Aceh are the targets of this counseling. The results of this community service program were that the elderly received information on the correctness and importance of maintaining a healthy and fit lifestyle to improve their health. The conclusion of this program was that after receiving this education, the elderly were able to apply a healthy and fit lifestyle in their older years in their daily lives.